برِعظیم میں فارسی مکتوب نگاری کی روایت - Azmat Hayat (Tabeer e Nau, 2025)
With the establishment of Muslim rule in India, Persian language and literature began to flourish. Masood Saad Sulaiman Lahori emerged as the first prominent Persian poet, while Hazrat Ali Hajveri is recognized as the first Persian prose writer. Under their influence, a significant number of writers in both Persian poetry and prose emerged, providing Persian with a strong foundation to thrive. Although most of the sultans of the Delhi Sultanate were of Turkish origin, their familiarity with Persian led them to adopt it for the administrative needs of the Sultanate and the royal court. Besides Delhi, cities like Lahore, Gujarat, and the Deccan also became known as major centers of Persian culture during the Sultanate era. With the spread of Persian, many poets and writers across different regions adopted it as their medium of expression. The literature of the royal courts attracted significant works from Iran, Afghanistan, and Central Asia, where they received official patronage. Alongside Persian poetry, Persian epistles and letters underwent a transformation, with significant contributions such as Amir Khusro's Ejaz-i Khusravi and Mahmood Gavan's Manazir Ul Insha, both of which hold historical importance. Later, writers like Hakeem Yusufi, Abul Fazl, Faizi, and other notable epistolary writers further enriched the Persian literary tradition, creating a flourishing period for Persian prose. Faizi, in particular, initiated a movement to simplify the complex narrative style, reduce Arabic influence, and make the language more accessible. This movement led to a shift toward writing in a simpler and more direct style, influencing writers such as Abul Fateh Gilani, Chandrabhan Brahman, Muhammad Saleh Kanboh, and even the emperor Aurangzeb Alamgir. Additionally, Sufis like Hazrat Mujaddid Alf Sani, through their works in Persian, contributed to the development of a more straightforward and expressive form of Persian prose. This article provides an overview of the tradition of Persian letter writing in India, explores the various styles within this genre, and introduces some of the most important Persian epistolary writers.